KEHIDUPAN DAMAI SEORANG MUSLIM: Implementasi Beragama dalam Tatanan Kehidupan Lingkungan Individu dan Sosial Kemasyarakatan - Khotimah, Husnul; Salsabila, Sabrina Libra; Sabiliyana, Rafika; Sabil, Muh. Alief; Hilman Kamil, Muhammad; Arifianto, M. Faris; Azizah, Nia Nur; Mujiono, Mujiono; Prakoso, Dicky Dwi (Moderation | Journal of Islamic Studies Review, 2024)
The role of religion in the life of individuals functions as a value system that contains certain norms. Religion is influential as a motivation in encouraging individuals to carry out an activity, because actions carried out against the background of religious beliefs are considered to have elements of purity, and obedience. Religion in the life of the individual also functions as 1). Sources of value in maintaining decency 2). As a means to overcome frustration, 3). As a means to satisfy curiosity. Furthermore, it deals with the function of religion in social life. Society is a composite of groups of individuals formed on the basis of a certain social order. The problem of religion will not be separated from the life of society, because religion itself turns out to be necessary in social life. In practice, the functions of religion in society include: 1). Educational function, 2). Savior, 3) As Atonement, 4). As Social Control, 5). As a Foster Sense of Solidarity. 6). Transformative Functioning, 7). Creative Functioning, 8). Sublimative Functioning, and 9). Sublimative functioning. Furthermore, related to human prosperity and happiness according to Islamic teachings, it can be seen from various sides, including 1). Human Social Obligations, 2). Man as Prosperity, and 3). Life Strategies as a Winner.